Enhanced Antitumor Activity of Lidocaine Nanoparticles Encapsulated by a Self-Assembling Peptide - Yang, Yang; Sun, Jiaxiao; Peng, Fei; Liu, Haibei; Zhao, Guoyan; Chen, Junjie; Zhang, Wensheng; Qiu, Feng (Frontiers in Pharmacology, 2022)
Although local anesthetics (LAs) such as lidocaine have been traditionally used for pain relief, their antitumor activity has attracted more and more attentions in recent years. However, since nearly all LAs used in clinic are in their hydrochloride forms with small molecular weight and high water-solubility, their fast absorption and clearance greatly limit their antitumor activity in vivo. To better exploit the antitumor activity of LAs, lidocaine nanoparticles (LNPs) are prepared by using a self-assembling peptide to encapsulate the hydrophobic base form of lidocaine. In cultured A375 human melanoma cells, the LNPs show much higher cellular uptake level than the clinic formulation of lidocaine hydrochloride, which leads to enhanced efficacy in inhibiting the proliferation, migration and invasion of the cells, as well as in inducing cell apoptosis. Compared with lidocaine hydrochloride, LNPs can also significantly slow down the release rate of lidocaine. In nude mice, LNPs can effectively inhibit the development of solid tumors from seeded A375 cells and prevent the recurrence of tumors after surgical excision. These results indicate that by using self-assembling peptide to fabricate nanoparticle formulations of local anesthetics, their antitumor activity can be significantly enhanced, suggesting a potential postoperative treatment to prevent tumor recurrence after surgical excision.